Comprehensive analysis of Tri-star toothbrush & Co.’s supply chain - Adnan, Waheduz Jaman (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.